2020
DOI: 10.3390/mi11040450
|View full text |Cite
|
Sign up to set email alerts
|

Polymer-Based Functional Cantilevers Integrated with Interdigitated Electrode Arrays—A Novel Platform for Cardiac Sensing

Abstract: Heart related ailments are some of the most common causes for death in the world, and some of the causes are cardiac toxicity due to drugs. Several platforms have been developed in this regard over the years that can measure electrical or mechanical behavior of cardiomyocytes. In this study, we have demonstrated a biomedical device that can simultaneously measure electrophysiology and contraction force of cardiomyocytes. This dual-function device is composed of a photosensitive polymer-based cantilever, with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…The final note of interest is the number of papers in recent years that overlap between two different sensors. This includes the use of: dielectrophoresis and ECIS [ 170 ], microcantilevers and ECIS [ 180 ], QCM and ECIS [ 125 ], microcantilevers and photoacoustics [ 58 ]. The benefit of these systems being that it is easier to correctly distinguish two separate species with two sets of tests to compare.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The final note of interest is the number of papers in recent years that overlap between two different sensors. This includes the use of: dielectrophoresis and ECIS [ 170 ], microcantilevers and ECIS [ 180 ], QCM and ECIS [ 125 ], microcantilevers and photoacoustics [ 58 ]. The benefit of these systems being that it is easier to correctly distinguish two separate species with two sets of tests to compare.…”
Section: Discussionmentioning
confidence: 99%
“…Platforms to easily measure this response would significantly increase efficiency. Kanade et al have demonstrated a platform for simultaneous mechanical and electrical monitoring of cardiomyocytes, using a microcantilever combined with ECIS [ 180 ]. Multiple sensor platforms such as lab-on-a-chip (LOC) technologies are becoming increasingly prevalent with the advancement and integration of microfluidics and relatively low-cost and facile production methods such as aerosol-jet printing [ 181 ] and inkjet printing [ 182 , 183 ].…”
Section: Electrical Biosensorsmentioning
confidence: 99%
“…Over the years, numerous devices and techniques have been developed to measure the cardiotoxicity caused by potential drugs. Several studies have presented interesting techniques to measure the drug-induced cardiac contractility. Atomic force microscopy (AFM) is a technique that employs a microcantilever tip to scan the surface of a cardiomyocyte and measure the contraction force. Cantilever-based techniques have been used for studying human pluripotent stem-derived cardiomyocyte-based tissue, embryoid bodies, and for neonatal rats’ ventricular myocytes (NRVMs) upon mechanical stimulation. Ossola et al combined AFM with a patch clamp technique, whereas Gaitas et al developed a polyimide (PI)-based microcantilever for sensing cardiac contractility of a single cell. , Pribyl et al utilized a silicon nitride cantilever to develop an AFM-based cardiac biosensing platform .…”
mentioning
confidence: 99%
“…In this Special Issue, 10 technical papers are published on piezoelectric devices [ 1 , 2 , 3 , 4 ], biomedical devices [ 5 , 6 ], micromachining [ 7 , 8 ], and complementary metal-oxide-semiconductor (CMOS) logic devices [ 9 , 10 ]. For the piezoelectric devices, high-density piezoelectric micromachined ultrasonic transducer array based on patterned aluminum nitride thin film is introduced for imaging application [ 1 ].…”
mentioning
confidence: 99%
“…Two papers investigate polymer-based functional cantilevers integrated with interdigitated electrode arrays and magnetic microfluidic pump for novel cardiac sensing and in vivo bone remodeling application, respectively [ 5 , 6 ]. Reference [ 5 ] demonstrates a biomedical device that can simultaneously measure electrophysiology and contraction force of cardiomyocytes using a photosensitive polymer-based cantilever, with a pair of metal-based interdigitated electrodes on its surface. A magnetically operated implantable microfluidic pump is introduced for in vivo studies of bone intramedullary fluid modulation for the potential application in bone density augmentation study in rat femora [ 6 ].…”
mentioning
confidence: 99%